Politik Hukum Pengaturan Retribusi Perizinan Tertentu dalam Hubungan Keuangan Pusat dan Daerah - Rini, Wafia Silvi Dhesinta; Kalo, Andi Muhammad Resky (Universitas Jember, 2023)
This research aims to determine the dynamics of changes in the regulation of certain types of licensing fees after the enactment of Law Number 1 of 2022 concerning Central and Regional Financial Relations. The results of this research show that first, Law Number 1 of 2022 concerning Central and Regional Financial Relations (UU HKPD) revokes the previous law, namely Law Number 28 of 2009 concerning Regional Taxes and Regional Levies. Second, the HKPD Law regulates levies for Building Approval (PBG), Use of Foreign Workers (PTKA), and Mining Management. Third, the legal politics of changes to certain licensing levy regulations are motivated by several reasons, including: (a) efforts to synchronize the Job Creation Law and the HKPD Law; (b) Academic texts of the Job Creation Law and the HKPD Law which are not comprehensive; (c) policy of simplifying licensing mechanisms and requirements to strengthen the investment climate. The legal policy of issuing the HKPD Law has had juridical implications for regions, such as a reduction in regional autonomy authority because several permits which are the basis for regional levies have been withdrawn by the central government. This makes the authority to impose licensing fees centralized and results in a reduction in the potential for Regional Original Income.Keywords: Licensing Levy, Legal Politics, Central and Regional Financial Relations.